(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1985)
?Iron Age skeletons at top of mound; cist with cremation. Long before that, Beaker sherds were placed in pit by old mound. Beneath mound, many sherds, cremated bones, and flints in thick black layer. Pollen, soil, and 14C dates indicate early Neo agriculture by people with Grimston/Lyles Hill wares.